Short Segment Spinal Instrumentation With Index Vertebra Pedicle Screw Placement for Pathologies Involving the Anterior and Middle Vertebral Column Is as Effective as Long Segment Stabilization With Cage Reconstruction: A Biomechanical Study. Issue 22 (November 2015) - Bartanusz, Viktor; Harris, Jonathan; Moldavsky, Mark; Cai, Yiwei; Bucklen, Brandon
Abstract : Study Design: An in vitro, cadaveric biomechanical study. Objective: The aim of the present study was to compare single-segment posterior instrumentation and fracture-level screws with single/multilevel posterior fixation and corpectomy in a simulated, unstable burst fracture model. Summary of Background Data: The optimal extent of instrumentation for surgical cases of non-neoplastic vertebral body pathologies remains uncertain. Although several clinical studies demonstrate advantages of short segment instrumentation with index-level screws over more extensive corpectomy and anterior–posterior techniques, a comprehensive biomechanical comparison of these techniques is currently lacking. Methods: Six bovine spines (T11–L5) were tested in flexion, extension, lateral bending (LB), and axial rotation (AR) following simulated burst fracture at L2. Posterior instrumentation included 1 level above/below (1LF) and 2 levels above/below fracture level (2LF), intermediate or index screws at fracture level (FF), and cross-connectors above/below fracture level (CC). Anterior corpectomy devices included expandable corpectomy spacers with/without integrated screws, ACDi and ACD, respectively FORTIFY-Integrated/FORTIFY; Globus Medical, Inc., PA. Constructs were tested in the following order: (1) Intact; (2) 1LF; (3) 1LF and CC; (4) 1LF and FF; (5) 1LF, CC, and FF; (6) 2LF; (7) 2LF and CC; (8) 2LF and FF; (9) 2LF, CC, and FF; (10) 2LF and ACD; (11) 2LF, ACD, and CC; (12) 1LF and ACDi; (13) 1LF, ACDi, and CC. Results: During flexion, all constructs except 1LF reduced motion relative to intact ( P ⩽ 0.05). Anterior support was most stable, but no differences were found between constructs ( P ≥ 0.05). Every construct reduced motion in extension, though no differences were found between constructs and intact ( P ≥ 0.05). During LB, all constructs reduced motion relative to intact ( P ⩽ 0.05); 2LF constructs further reduced motion ( P ⩽ 0.05). No construct returned AR motion to intact, with significant increases in 1LF and ACDi, 2LF and ACD, and 2LF, ACD, and CC ( P ⩽ 0.05). Cross-connectors and fracture screws reinforced each other in posterior-only constructs, providing maximum stability ( P ≥ 0.05). Conclusions: This biomechanical comparison study found no significant superiority of combined anterior–posterior constructs over short segment fracture screw fixation, only multilevel posterior instrumentation with and without anterior support, providing increased stability in LB. Biomechanical equivalency suggests that short segment fracture screw intervention may provide appropriate stabilization for non-neoplastic pathologies involving the anterior and middle vertebral columns. Level of Evidence: 2